2018
DOI: 10.1002/pbc.27281
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of invasive mucormycosis with isavuconazole in pediatric patients

Abstract: Based on our limited clinical experience, isavuconazole may be a safe and effective treatment option for children and adolescents afflicted by IMI. Prospective clinical trials should be performed in order to evaluate the pharmakokinetics and safety of isavuconazole in the pediatric population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 23 publications
2
23
0
Order By: Relevance
“…Altogether, pharmacokinetics studies obtained from these patients suggest that a lower dosage of ISAV is not appropriate for the management of paediatric patients. Indeed, higher drug clearance rate and shorter half-life of ISAV in children as compared with adults may explain lower trough levels obtained in these three cases [2]. The final dosage for two paediatric cases was 200 mg/day, the 7-year-old girl received a higher dose increased to 2 × 200 mg/day.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Altogether, pharmacokinetics studies obtained from these patients suggest that a lower dosage of ISAV is not appropriate for the management of paediatric patients. Indeed, higher drug clearance rate and shorter half-life of ISAV in children as compared with adults may explain lower trough levels obtained in these three cases [2]. The final dosage for two paediatric cases was 200 mg/day, the 7-year-old girl received a higher dose increased to 2 × 200 mg/day.…”
Section: Discussionmentioning
confidence: 92%
“…Recently, the use of ISAV in three young children, between 4.5 and 7 years of age having developed mucormycosis, has been reported [2,3]. For two of them, the initial dose of ISAV was lower than that in adult, 80 and 100 mg/ day, respectively.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Four papers described 6 pediatric cases successfully treated with ISA for proven mucormycosis (14)(15)(16)(17). In the studies described in the literature, as summarized in Table 5, ISA was used as a rescue treatment in 4/6 patients, and in two-thirds of the cases, ISA was used as part of combination therapy; most patients also underwent surgical debridement.…”
Section: Discussionmentioning
confidence: 99%
“…The triazole drug isavuconazole has activity against Mucorales moulds, and a recent single‐arm, open‐label trial in adults showed that isavuconazole had similar all‐cause mortality to LAmB (Marty et al ., ). The safety and efficacy of isavuconazole in paediatric patients have not been established, but isavuconazole has been used successfully to treat mucormycosis in children (Barg et al ., ). A clinical trial is ongoing to determine the optimal delivery of isavuconazole in paediatric patients (ClinicalTrials.gov: NCT 03241550).…”
Section: Treatment Of Ifdmentioning
confidence: 97%